Climate change and its mitigation in agricultural country - Resda, Cicilya Dolfiana (Institute for Advanced Science, Social, and Sustainable Future, 2024)
Background: This research aims to discuss climate change and its mitigation and adaptation, especially in the agriculture sector. It will help in formulating and managing this sector if someday there are so many cases that make a mess in this sector. Methods: This research is conducted as qualitative research. Finding: Agriculture holds some important rules for a country, humans, and other living organisms. Indonesia as an agricultural country has so many sources that are impacted by climate change. Climate change is affecting so many aspects. Agriculture is one of the greatest things that will get the serious impact from climate change. In global, agriculture gives about 14% of the total emissions, and in national, it gives about 12%. Although it seems little the negative impacts are felt by the living organisms. The impacts of climate change need active efforts to anticipate it through mitigation and adaptation strategies. Conclusion: The mitigation technology will reduce greenhouse gas and the agriculture field by using low-emission varieties, water, and land management technology.